1981
DOI: 10.1001/jama.1981.03320060042020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ingestion of Meat on Plasma Cholesterol of Vegetarians

Abstract: In a controlled trial, 21 strict vegetarians were studied prospectively for eight weeks: a two-week control period of the usual vegetarian diet was followed by four weeks, during which 250 g of beef was added isocalorically to the daily vegetarian diet and then by two weeks of the control diet. Plasma high-density lipoprotein-cholesterol did not change during the study, whereas plasma total cholesterol rose significantly by 19% at the end of the meat-eating period. Systolic blood pressure (BP) increased signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 16 publications
1
18
0
1
Order By: Relevance
“…In the same study, for 45-to 64-yearold men, there was approximately a threefold difference in risk between men who ate meat daily and those who did not eat meat. Finally, regular consumption of beef, when added to a vegetarian diet, has been demonstrated to increase blood cholesterol, especially LDL, and blood pressure (Sacks et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, for 45-to 64-yearold men, there was approximately a threefold difference in risk between men who ate meat daily and those who did not eat meat. Finally, regular consumption of beef, when added to a vegetarian diet, has been demonstrated to increase blood cholesterol, especially LDL, and blood pressure (Sacks et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Meat fat contains saturated fatty acids which increase LDL-C. 321 (1+) Meat fat should be limited in those seeking to lower cardiovascular risk. Most processed meats or meat products, such as sausage, saveloy, luncheon meat, paté and salami, are high in saturated fatty acids.…”
Section: Meat and Meat Productsmentioning
confidence: 99%
“…Regarding animal protein intake, a small study 40 reported increased systolic blood pressure with 250 g of beef per day added to the diets of normotensive vegetarians for 4 weeks. However, other similar small studies 41,42 found no effect on blood pressure.…”
Section: Commentmentioning
confidence: 99%